Highly Sensitive Method to Isolate Photocurrent Signals from Large Background Redox Currents on Protein‐Modified Electrodes. Issue 11 (3rd April 2019) - Jun, Daniel; Beatty, J. Thomas; Bizzotto, Dan
Abstract: The high quantum efficiency in converting light energy into a charge‐separated state is a major advantage in using photosynthetic proteins in biophotovoltaic applications. Photocurrents are typically measured at open circuit potential (OCP), where the electrochemical redox or faradaic currents are minimized. However, at potentials far from the OCP, the photocurrents produced by the proteins may be impossible to measure against the large background current, owing to electrochemical redox reactions of charge‐transfer mediators and/or sacrificial electron donors. Demonstrated here is a highly sensitive method using a sinusoidal‐modulated intensity of an LED excitation light source to isolate the protein‐based photocurrent component from the total current irrespective of electrode surface coverage. Using a genetically modified photochemical reaction center from Rhodobacter sphaeroides as a proof‐of‐concept, photocurrents up to 10 4 –10 5 orders of magnitude smaller than the background electrochemical redox current (due to redox reactions directly on the electrode surface) were measured at applied voltages >0.4 V from the OCP. The phase relationship between the optical excitation and photocurrent response was also measured and shown to be analytically useful. Abstract : Isn′t it exciting ! A method to accurately detect photocurrent signals 10 4 –10 5 ‐fold smaller than background currents is presented. Bacterial photosynthetic reaction center proteins are bound to a gold electrode and optically excited at 13 Hz, resulting in electron transfer through the protein and to the electrode (see picture, arrows). A photocurrent signal is detected at the same frequency as the excitation signal and isolated from the background current.